Chemical doping enhances electronic transport in networks of hexabenzocoronenes assembled in non-aqueous electrolyte1. Issue 31 (21st August 2015) - Gerber, Laura C. H.; Frischmann, Peter D.; Williams, Teresa E.; Tichelaar, Martijn; Tsai, Erica Y.; Liu, Yi-Sheng; Guo, Jinghua; Pemmaraju, C. D.; Prendergast, David; Helms, Brett A.
<x xml:space="preserve">Abstract</x> The electronic transport properties of HBC networks in non-aqueous electrolyte are tailored using synthetic chemistry and supramolecular design principles.